Positive electrode active material, preparation method thereof and lithium secondary battery containing the same
By using a coating containing niobium compounds in the positive electrode active material of the lithium secondary battery, the problems of structural collapse and low thermal stability of the existing positive electrode active material during charging and discharging are solved, and the high temperature of the lithium secondary battery is achieved Improved life characteristics and resistance performance.
Patent Information
- Application Number
- CN202080088782.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-20
- Filing Date
- 2020-12-18
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2040-12-18
AI Technical Summary
The existing layered cathode active materials are prone to structural collapse during charging and discharging, and have low thermal stability and are difficult to commercialize.
Using a coating containing niobium compounds is located on the surface of primary particles and secondary particles of the lithium secondary battery, lithium metal oxide particles in the form of secondary particles containing multiple primary particles and form a first coating on the surface thereof and The second coating, the first coating comprises a first niobium compound, and the second coating comprises a first niobium compound and a second niobium compound having different components.
The high-temperature life characteristics of lithium secondary batteries are achieved and the resistance increase rate is reduced, which significantly improves the initial efficiency and resistance performance of the battery.
Smart Images

Figure CN114868281B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode active material, a preparation method thereof and a lithium secondary battery comprising the same. Background Art
[0002] In recent years, with the explosive growth in demand for IT mobile devices and small electric drive devices (electric bicycles, small EVs, etc.) and the increasing demand for electric vehicles with a range of more than 400 km, research and development of secondary batteries with high capacity and high energy density are actively carried out worldwide.
[0003] In order to prepare such a high-capacity battery, it is necessary to use a high-capacity positive electrode active material.
[0004] Among existing layered cathode active materials, the one with the highest capacity is LiNiO2 (275 mAh / g), but it is prone to structural collapse during charge and discharge, and has low thermal stability due to oxidation number problems, making it difficult to commercialize in practice.
[0005] In order to solve this problem, the unstable Ni sites must be replaced by other stable transition metals (Co, Mn, etc.). For this purpose, a ternary NCM system substituted with Co and Mn was developed. Summary of the invention
[0006] Technical issues
[0007] This embodiment aims to provide a positive electrode active material in which a coating layer containing a niobium compound is located on the surface of primary particles and secondary particles, thereby having high temperature life characteristics and reducing the resistance increase rate.
[0008] Technical Solution
[0009] According to one embodiment, the positive active material of a lithium secondary battery may be a lithium metal oxide particle in the form of a secondary particle containing a plurality of primary particles, and the positive active material may include: a first coating layer located on at least a portion of the surface of the primary particle; and a second coating layer located on at least a portion of the surface of the secondary particle, wherein the first coating layer may include a first niobium compound, and the second coating layer may include the first niobium compound and a second niobium compound having a composition different from that of the first niobium compound.
[0010] According to another embodiment, a method for preparing a positive electrode active material for a lithium secondary battery may include: a step of preparing a niobium-containing coating composition; a step of mixing a metal precursor and a lithium raw material and calcining them to obtain a calcined body; a step of adding the coating composition and the calcined body to prepare a mixture; and a step of drying the mixture and heat treating it, wherein the heat treatment may be performed at 100 to 500 degrees.
[0011] A lithium secondary battery according to still another embodiment may include: a positive electrode including the positive electrode active material according to one embodiment; a negative electrode; and a nonaqueous electrolyte.
[0012] Effects of the Invention
[0013] According to a positive electrode active material of one embodiment, a lithium secondary battery having excellent initial efficiency and initial resistance can be realized by including a first coating layer located on the surface of a primary particle and including a first niobium compound, and a second coating layer located on the surface of the secondary particle and including the first niobium compound and a second niobium compound of a different composition.
[0014] In addition, the lithium secondary battery using the positive electrode active material not only has excellent high-temperature life characteristics, but also can significantly reduce the resistance increase rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1a The 0.1C discharge capacity and the initial resistance value according to the niobium content are shown.
[0016] Figure 1b The 0.1C discharge capacity and the initial resistance value according to the secondary heat treatment temperature when the niobium content is 2000 ppm are shown.
[0017] Figure 2a The life span and the resistance increase rate at high temperatures according to the niobium content are shown.
[0018] Figure 2b The high temperature life and the high temperature resistance increase rate according to the secondary heat treatment temperature when the niobium content is 2000 ppm are shown.
[0019] Figure 3a to Figure 3c A cross-sectional photograph of the positive electrode active material prepared according to Example 3, an element mapping result of the cross section, and a line scanning analysis result of the primary particle interface are respectively shown.
[0020] Figure 4 The structural analysis results of the primary particle interface of the positive electrode active material prepared according to Example 3 are shown.
[0021] Figure 5a and Figure 5b A cross-sectional photograph of the positive electrode active material prepared according to Example 3 and a detection result of whether the primary particle interface in the cross-section contains lithium using EELS are respectively shown.
[0022] Figure 6 The SEM and EDS analysis results of the surface of the positive electrode active material prepared according to Example 3 are shown.
[0023] Figure 7 The element mapping results of the cross section of the positive electrode active material prepared according to Example 3 are shown.
[0024] Figure 8 The results of structural analysis of the secondary particle surface portion of the cross section of the positive electrode active material prepared in Example 3 using TEM analysis are shown. DETAILED DESCRIPTION
[0025] The words first, second, third, etc. herein are used to describe various parts, components, regions, layers, and / or segments, but these parts, components, regions, layers, and / or segments should not be limited by these words. These words are only used to distinguish a certain part, component, region, layer, and / or segment from another part, component, region, layer, and / or segment. Therefore, without departing from the scope of the present invention, the first part, component, region, layer, and / or segment described below can also be described as the second part, component, region, layer, and / or segment.
[0026] The terms used herein are only for describing specific embodiments and are not intended to limit the present invention. Unless the context otherwise clearly indicates the opposite, the singular form used herein is also intended to include the plural form. "Including" used in the specification may specifically refer to a certain characteristic, field, integer, step, action, element and / or component, but does not exclude the existence or addition of other characteristics, fields, integers, steps, actions, elements, components and / or groups.
[0027] If a part is described as being "on" another part, it may be directly on the other part or there may be other parts therebetween. When a part is described as being "directly on" another part, there may be no other parts therebetween.
[0028] Although not otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. Terms defined in dictionaries should be interpreted as having the same meaning as that disclosed in the relevant technical literature and this article, and should not be interpreted in an idealized or overly formal sense.
[0029] In addition, unless otherwise specified, % means weight %, and 1 ppm means 0.0001 weight %.
[0030] The embodiments of the present invention are described in detail below so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various different ways and is not limited to the embodiments described herein.
[0031] A positive electrode active material according to one embodiment includes lithium metal oxide particles.
[0032] The lithium metal oxide particles are in the form of secondary particles including a plurality of primary particles.
[0033] The positive electrode active material of this embodiment has a first coating layer on at least a portion of the surface of the primary particles, and a second coating layer on at least a portion of the surface of the second particles.
[0034] The first coating layer comprises a first niobium compound and the second coating layer comprises a first niobium compound and a second niobium compound. The second niobium compound has a different composition than the first niobium compound in the first coating layer.
[0035] The primary particle where the first coating is located refers to the primary particle located inside the secondary particle. Therefore, the surface of the primary particle where the first coating is located does not include the surface of the primary particle exposed outside the secondary particle.
[0036] As described above, the first coating layer containing the first niobium compound is located on the surface of the primary particles, and the primary particles are located inside the secondary particles, and the second coating layer is located on the surface of the secondary particles, and the second coating layer contains the first niobium compound and also contains a second niobium compound having a different component from the first niobium compound, so that the initial resistance at room temperature and the resistance increase rate at high temperature can be significantly reduced.
[0037] On the other hand, at least one of the first niobium compound and the second niobium compound contains an amorphous structure. Such an amorphous niobium compound has excellent ion conductivity. Therefore, when there is a first coating layer containing a first niobium compound with an amorphous structure and a second coating layer containing at least two niobium compounds, a battery having excellent initial efficiency at room temperature and high temperature can be realized. In addition, the initial resistance at room temperature and the resistance increase rate at high temperature can be significantly reduced.
[0038] The first niobium compound may be at least one of Nb2O5, NbO and NbO2.
[0039] In addition, the second niobium compound may be at least one of LiNbO3, Nb2O5, Li3NbO4 and LiNb3O8.
[0040] The average thickness of the first coating layer is less than the average thickness of the second coating layer.
[0041] Specifically, the average thickness of the first coating layer may be less than 5 nm, more specifically 0.01 nm to 5 nm, 0.5 nm to 3 nm. When the average thickness of the first coating layer satisfies the above range, the initial resistance at room temperature and the resistance increase rate at high temperature can be reduced.
[0042] In addition, the average thickness of the second coating layer may be 30 nm or less, more specifically 1 nm to 30 nm or 3 nm to 25 nm. When the average thickness of the second coating layer satisfies the above range, the initial resistance at room temperature and the resistance increase rate at high temperature may be reduced.
[0043] In this embodiment, the second niobium compound included in the second coating layer may be LiNbO3. At this time, the content of LiNbO3 may be 15.7at% or more, more specifically 15.7at% to 30at% or 15.7at% to 20at% based on the entire second coating layer. When the content of LiNbO3 included in the second coating layer satisfies the above range, the initial resistance at room temperature and the resistance increase rate at high temperature can be significantly reduced.
[0044] On the other hand, in the positive electrode active material of the present embodiment, the content of niobium (Nb) may be 4000ppm or less, more specifically 1000ppm to 2500ppm or 1000ppm to 3000ppm, based on the total positive electrode active material. When the content of niobium satisfies the range, the initial resistance at room temperature and the resistance increase rate at high temperature can be significantly reduced.
[0045] On the other hand, in this embodiment, the content of nickel in the metal in the lithium metal oxide may be 80 mol % or more. More specifically, for example, the lithium metal oxide may be represented by the following Chemical Formula 1.
[0046] [Chemical formula 1]
[0047] Li x Ni a Co b Mn c M1 d M2 e O2
[0048] In the chemical formula 1, M1 and M2 are each at least one of Zr, Ti, Mg, Al, Ni, Mn, Zn, Fe, Cr, Mo and W, x is 0.90≤x≤1.07, a is 0.80≤a<1, b is 0<b≤0.3, c is 0<c≤0.3, d is 0<d<0.01, e is 0<e<0.01, and a+b+c+d+e=1.
[0049] At this time, the a is 0.85≤a<1, and more specifically, may be 0.90≤a<1.
[0050] In addition, the b may be 0<b≤0.2 or 0<b≤0.1, and c may be 0<c≤0.2 or 0<c≤0.1. Meanwhile, the M1 may be Zr, and the M2 may be Al. When M1 is Zr and M2 is Al, the positive electrode active material of this embodiment may contain 3000ppm to 4000ppm of Zr and 200ppm to 350ppm of Al based on the total lithium metal oxide.
[0051] As described in this embodiment, when the nickel content in the metal in the lithium metal oxide is 80% or more, that is, when a in Chemical Formula 1 is 0.80 or more, a positive electrode active material with high output characteristics can be realized. The positive electrode active material of this embodiment having these components has a higher energy density per unit volume, so the capacity of the battery using the positive electrode active material can be increased, and it is suitable for use in electric vehicles.
[0052] Secondly, the lithium metal oxide may include a core and a shell located on the surface of the core. Both the core and the shell have a layered crystalline structure. In addition, in the lithium metal oxide, nickel has a concentration gradient from the core to the shell, and the region up to 95% of the length in the total radius of the lithium metal oxide may have a concentration gradient. In this case, when the nickel concentration of the core is 100mol%, the nickel concentration of the shell may gradually decrease to 50mol%. For convenience, the concentration gradient is described by taking nickel as an example, but the relevant description of the concentration gradient may also be applicable to the manganese and cobalt.
[0053] According to another embodiment, a method for preparing a positive electrode active material may include: preparing a niobium-containing coating composition; mixing a metal precursor and a lithium raw material and calcining them to obtain a calcined body; adding the coating composition and the calcined body to prepare a mixture; and drying the mixture and heat treating it.
[0054] First, the step of preparing the coating composition can be performed by adding ammonium niobium oxalate into distilled water and mixing.
[0055] Next, the step of mixing the metal precursor and the lithium raw material and then calcining to obtain a calcined body can be performed by preparing a lithium metal oxide precursor and then preparing a raw material of a doping element and mixing them according to the method described in the following examples.
[0056] The calcination may be performed by a conventional method, and specifically may include calcination, cooling and pulverization processes.
[0057] Next, a step of adding the coating composition and the calcined body to prepare a mixture is performed.
[0058] The step of preparing a mixture may be performed by a method in which the coating composition is used as a water washing liquid.
[0059] The step of preparing the mixture and then drying it for heat treatment may be included. In this embodiment, the heat treatment may be performed at 100 to 500 degrees, more specifically at 200 to 450 degrees, 250 to 400 degrees, or 300 to 350 degrees.
[0060] The heat treatment time of the heat treatment step may be 3 hours to 10 hours or 5 hours to 10 hours.
[0061] The heat treatment temperature and time are appropriate temperature and time ranges for removing the water remaining on the surface of the positive electrode active material subjected to the water washing treatment with the coating composition and not reducing the high temperature life characteristics. In addition, when such a range is satisfied, a positive electrode active material can be prepared, in which a first coating layer containing a niobium compound is formed on the surface of a plurality of primary particles, and a second coating layer containing a niobium compound having a different component from the niobium compound of the first coating layer is formed on the surface of the secondary particles.
[0062] These process conditions are described in more detail in the following examples.
[0063] In another embodiment of the present invention, a lithium secondary battery is provided, which includes: a positive electrode, the positive electrode including the positive electrode active material according to one embodiment of the present invention; a negative electrode, the negative electrode including the negative electrode active material; and an electrolyte, the electrolyte being located between the positive electrode and the negative electrode.
[0064] The description of the positive electrode active material is the same as that of the aforementioned embodiment of the present invention, and thus will not be repeated herein.
[0065] The positive electrode active material layer may include a binder and a conductive material.
[0066] The binder plays a role in allowing the positive electrode active material particles to be well bonded to each other and allowing the positive electrode active material to be well bonded to the current collector.
[0067] The conductive material is used to impart conductivity to the electrode, and any conductive material may be used as long as it does not cause chemical changes in the constituted battery.
[0068] The negative electrode includes a current collector and a negative electrode active material layer formed on the current collector, wherein the negative electrode active material layer includes a negative electrode active material.
[0069] As the negative electrode active material, a substance capable of reversibly intercalating / deintercalating lithium ions, lithium metal, an alloy of lithium metal, a substance capable of doping and dedoping lithium, or a transition metal oxide may be used.
[0070] As the substance capable of reversibly inserting and extracting lithium ions, any carbon-based negative electrode active material generally used as a carbon substance in lithium ion secondary batteries can be used, and as a typical example thereof, crystalline carbon, amorphous carbon, or a combination thereof can be used.
[0071] As the alloy of the lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn can be used.
[0072] Examples of the substance capable of lithium doping and dedoping include Si, SiO x (0<x<2), Si-Y alloy (the Y is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements and combinations thereof, but not Si), Sn, SnO2, Sn-Y (the Y is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements and combinations thereof, but not Sn), etc.
[0073] Examples of the transition metal oxide include vanadium oxide, lithium vanadium oxide, etc. The negative electrode active material layer also includes a binder and may further include a conductive material.
[0074] The binder plays a role in allowing negative electrode active material particles to be well bonded to each other and allowing the negative electrode active material to be well bonded to the current collector.
[0075] The conductive material is used to impart conductivity to the electrode, and any conductive material may be used as long as it does not cause chemical changes in the constituted battery.
[0076] As the current collector, a material selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer material coated with a conductive metal, and a combination thereof may be used.
[0077] For the negative electrode and the positive electrode, an active material, a conductive material and a binder are mixed in a solvent to prepare an active material composition, and the composition is coated on a current collector to prepare the negative electrode and the positive electrode. Such an electrode preparation method is well known in the art, so a detailed description is omitted in this specification. As the solvent, N-methylpyrrolidone and the like can be used, but it is not limited thereto.
[0078] The electrolyte includes a nonaqueous organic solvent and a lithium salt.
[0079] The nonaqueous organic solvent functions as a medium through which ions participating in the electrochemical reaction of the battery can migrate.
[0080] The lithium salt is a material that functions as a lithium ion source in a battery when dissolved in an organic solvent, thereby ensuring the basic operation of a lithium secondary battery and promoting the migration of lithium ions between a positive electrode and a negative electrode.
[0081] Depending on the type of lithium secondary battery, a separator may also be present between the positive electrode and the negative electrode. As such a separator, polyethylene, polypropylene, polyvinylidene fluoride or a multilayer film of at least two layers thereof may be used, and of course mixed multilayer films such as polyethylene / polypropylene two-layer separators, polyethylene / polypropylene / polyethylene three-layer separators, polypropylene / polyethylene / polypropylene three-layer separators, etc. may be used.
[0082] For lithium secondary batteries, according to the types of separators and electrolytes used, they can be divided into lithium ion batteries, lithium ion polymer batteries and lithium polymer batteries. According to the shape, they can be divided into cylindrical, prismatic, coin and bag types. According to the size, they can be divided into block and film types. The structure and preparation method of these batteries are well known in the field, so they will not be described in detail.
[0083] Hereinafter, embodiments of the present invention will be described in detail. However, the following embodiments are merely examples, and the present invention is not limited to the following embodiments, and the scope of the present invention is subject to the claims.
[0084] Preparation Example 1-Preparation of a positive electrode active material precursor containing 88 mol% Ni
[0085] The positive electrode active material precursor is prepared by a general coprecipitation method. Specifically, the supplied solution is designed to have a core component of (Ni 0.98 Co 0.01 Mn 0.01 )(OH)2, the outer shell component is (Ni 0.64 Co 0.23 Mn 0.13 )(OH)2.
[0086] In addition, in order to form a CSG (Core Shell Gradient) structure, a first supply tank with a high Ni concentration and a second supply tank with a low Ni concentration are arranged in series. This is to keep the Ni concentration of the core constant and change the Ni concentration of the shell.
[0087] NiSO4.6H2O was used as a nickel raw material, CoSO4.7H2O was used as a cobalt raw material, and MnSO4.H2O was used as a manganese raw material. These raw materials were dissolved in distilled water to prepare a metal salt aqueous solution.
[0088] After the coprecipitation reactor was prepared, N2 was purged to prevent oxidation of metal ions during the coprecipitation reaction, and the reactor temperature was maintained at 50°C.
[0089] NH4(OH) was added as a chelating agent in the coprecipitation reactor, and NaOH was used to adjust the pH. The precipitate obtained according to the coprecipitation process was filtered, washed with distilled water, and dried in an oven at 100° C. for 24 hours to prepare a positive electrode active material precursor.
[0090] The components of the prepared precursor are (Ni 0.88 Co 0.095 Mn 0.025 )(OH)2, the average particle size (D50) is 14.8μm.
[0091] Comparative Example 1 - Preparation of a positive electrode active material containing 88 mol% Ni (without coating)
[0092] Based on 1 mol of the positive electrode active material precursor prepared in the preparation example 1, 1.05 mol of LiOH·H2O (Sanquan Chemical, battery grade), ZrO2 (Aldrich, 4N) and Al(OH)3 (Aldrich, 4N) were uniformly mixed and mixed to 3400 ppm of Zr and 280 ppm of Al to prepare a mixture.
[0093] The mixture is placed in a tube furnace and oxygen is introduced for calcination, then cooled to room temperature, and then pulverized to prepare a calcined body powder. The calcination conditions are heat treatment at 480°C for 5 hours and then maintained at 700 to 750°C for 16 hours, with a heating rate of 5°C / minute. Then, after cooling to room temperature, the calcined body powder is pulverized and classified to prepare a positive electrode active material containing lithium metal oxide particles, wherein the lithium metal oxide particles are in the form of secondary particles containing a plurality of primary particles.
[0094] Comparative Example 2 - Positive electrode active material coated with 500 ppm boron
[0095] Based on 1 mol of the positive electrode active material precursor prepared in the preparation example 1, 1.05 mol of LiOH·H2O (Sanquan Chemical, battery grade), ZrO2 (Aldrich, 4N) and Al(OH)3 (Aldrich, 4N) were uniformly mixed and mixed to 3400 ppm of Zr and 280 ppm of Al to prepare a mixture.
[0096] The mixture is placed in a tube furnace and oxygen is introduced for calcination, then cooled to room temperature, and then pulverized to prepare a calcined body powder. The calcination conditions are heat treatment at 480°C for 5 hours and then maintained at 700 to 750°C for 16 hours, with a heating rate of 5°C / minute. Then, after cooling to room temperature, the calcined body powder is pulverized and classified to prepare lithium metal oxide particles in the form of secondary particles containing a plurality of primary particles.
[0097] Next, for the water washing process, 100 g of the lithium metal oxide particles were added to 100 g of distilled water (DI water) and stirred for 10 minutes, and then filtered. The residual lithium on the surface of the lithium metal oxide particles after the water washing was removed by vacuum drying.
[0098] Then, the lithium metal oxide particles from which residual lithium was removed were dry-mixed with H3BO3 (Aldrich) at a weight ratio of 100:0.453 (lithium metal oxide particles: H3BO3), and then subjected to a secondary heat treatment at 300°C for 5 hours to prepare a positive electrode active material having a boron-containing coating formed on the surface of the lithium metal oxide particles.
[0099] Comparative Example 3 - Dry coating of 2000 ppm ammonium niobium oxalate
[0100] Based on 1 mol of the positive electrode active material precursor prepared in the preparation example 1, 1.05 mol of LiOH·H2O (Sanquan Chemical, battery grade), ZrO2 (Aldrich, 4N) and Al(OH)3 (Aldrich, 4N) were uniformly mixed and mixed to 3400 ppm of Zr and 280 ppm of Al to prepare a mixture.
[0101] The mixture is placed in a tube furnace and oxygen is introduced for calcination, then cooled to room temperature, and then pulverized to prepare a calcined body powder. The calcination conditions are heat treatment at 480°C for 5 hours and then maintained at 700 to 750°C for 16 hours, with a heating rate of 5°C / minute. Then, after cooling to room temperature, the calcined body powder is pulverized and classified to prepare lithium metal oxide particles in the form of secondary particles containing a plurality of primary particles.
[0102] Next, for the water washing process, 100 g of the lithium metal oxide particles were added to 100 g of distilled water (DI water) and stirred for 10 minutes, and then filtered. The residual lithium on the surface of the lithium metal oxide particles after the water washing was removed by vacuum drying.
[0103] Then, the lithium metal oxide particles from which residual lithium was removed were dry-mixed with 2000 ppm (in terms of Nb content) of ammonium niobium oxalate, and then subjected to a secondary heat treatment at 300° C. for 5 hours to prepare a positive electrode active material having a coating layer containing a niobium compound formed on the surface of the lithium metal oxide particles.
[0104] Comparative Example 4 - Dry coating of 2000 ppm Nb2O5
[0105] A positive electrode active material was prepared by the same method as 2) of Comparative Example 3, except that 2000 ppm (in terms of Nb content) of Nb2O5 was dry-mixed.
[0106] Reference Example 1 - Wet coating of 1000 ppm (based on Co content) Co(NO3)2
[0107] Based on 1 mol of the positive electrode active material precursor prepared in the preparation example 1, 1.05 mol of LiOH·H2O (Sanquan Chemical, battery grade), ZrO2 (Aldrich, 4N) and Al(OH)3 (Aldrich, 4N) were uniformly mixed and mixed to 3400 ppm of Zr and 280 ppm of Al to prepare a mixture.
[0108] The mixture is placed in a tube furnace and oxygen is introduced for calcination, then cooled to room temperature, and then pulverized to prepare calcined body powder. The calcination conditions are heat treatment at 480°C for 5 hours and then maintained at 700 to 750°C for 16 hours, with a heating rate of 5°C / min. Then, after cooling to room temperature, the calcined body powder is pulverized and classified to prepare lithium metal oxide particles.
[0109] Next, for the water washing process, 2.494 g (based on 1000 ppm of Co) of Co(NO3)2·6H2O was added to 100 g of distilled water (DIwater) and stirred for 10 minutes, and then 250 g of the lithium metal oxide particles were added and stirred for 10 minutes to obtain lithium metal oxide particles having a coating containing CoSO4 formed on the surface.
[0110] Then, the lithium metal oxide particles formed with the coating layer containing Co(NO 3 ) 2 were dried using a spray dryer and then subjected to a secondary heat treatment at 300° C. for 5 hours to prepare a positive electrode active material.
[0111] Reference Example 2 - Wet coating of 1000ppm (based on Co content) LiNO3+Co(NO3)2
[0112] A positive electrode active material was prepared by the same method as Reference Example 1 except that 2.494 g of Co(NO 3 ) 2 ·6H 2 O and 0.591 g of LiNO 3 were added to distilled water in the water washing process.
[0113] Example 1 - Wet coating of 1000 ppm ammonium niobium oxalate
[0114] Based on 1 mol of the positive electrode active material precursor prepared in the preparation example 1, 1.05 mol of LiOH·H2O (Sanquan Chemical, battery grade), ZrO2 (Aldrich, 4N) and Al(OH)3 (Aldrich, 4N) were uniformly mixed and mixed to 3400 ppm of Zr and 280 ppm of Al to prepare a mixture.
[0115] The mixture is placed in a tube furnace and oxygen is introduced for calcination, then cooled to room temperature, and then pulverized to prepare a calcined body powder. The calcination conditions are heat treatment at 480°C for 5 hours and then maintained at 700 to 750°C for 16 hours, with a heating rate of 5°C / minute. Then, after cooling to room temperature, the calcined body powder is pulverized and classified to prepare lithium metal oxide particles in the form of secondary particles containing a plurality of primary particles.
[0116] Next, for the water washing process, 0.7205 g of ammonium niobium oxalate was added to 100 g of distilled water (DI water) to make the Nb content 1000 ppm, and stirred for 10 minutes, and then 250 g of the lithium metal oxide particles were added and stirred for 10 minutes to obtain lithium metal oxide particles having a first coating layer containing a first niobium compound formed on the surface of the primary particles and a second coating layer containing the first niobium compound and the second niobium compound formed on the surface of the secondary particles.
[0117] Then, the lithium metal oxide particles were dried using a spray dryer and then subjected to a secondary heat treatment at 300° C. for 5 hours to prepare a positive electrode active material.
[0118] Example 2 - Wet coating of 2000 ppm ammonium niobium oxalate
[0119] In the water washing process, a positive electrode active material was prepared by the same method as in Example 1 except that 1.4409 g of ammonium niobium oxalate was added to distilled water.
[0120] Example 3 - Wet coating of 4000 ppm ammonium niobium oxalate
[0121] In the water washing process, a positive electrode active material was prepared by the same method as in Example 1 except that 2.8818 g of ammonium niobium oxalate was added to distilled water.
[0122] Example 4 - Wet coating of 8000 ppm ammonium niobium oxalate
[0123] In the water washing process, a positive electrode active material was prepared by the same method as in Example 1 except that 5.7637 g of ammonium niobium oxalate was added to distilled water.
[0124] Example 5 - Wet coating of 2000 ppm ammonium niobium oxalate
[0125] Based on 1 mol of the positive electrode active material precursor prepared in the preparation example 1, 1.05 mol of LiOH·H2O (Sanquan Chemical, battery grade), ZrO2 (Aldrich, 4N) and Al(OH)3 (Aldrich, 4N) were uniformly mixed and mixed to 3400 ppm of Zr and 280 ppm of Al to prepare a mixture.
[0126] The mixture is placed in a tube furnace and oxygen is introduced for calcination, then cooled to room temperature, and then pulverized to prepare a calcined body powder. The calcination conditions are heat treatment at 480°C for 5 hours and then maintained at 700 to 750°C for 16 hours, with a heating rate of 5°C / minute. Then, after cooling to room temperature, the calcined body powder is pulverized and classified to prepare lithium metal oxide particles in the form of secondary particles containing a plurality of primary particles.
[0127] Next, for the water washing process, 1.4409 g of ammonium niobium oxalate was added to 100 g of distilled water (DI water) to make the Nb content 2000 ppm (based on the prepared positive electrode active material), and stirred for 10 minutes, and then 250 g of the lithium metal oxide particles were added and stirred for 10 minutes to obtain lithium metal oxide particles having a first coating layer containing a first niobium compound formed on the surface of the primary particles and a second coating layer containing the first niobium compound and the second niobium compound formed on the surface of the secondary particles.
[0128] Then, the lithium metal oxide particles are dried using a spray dryer to prepare a positive electrode active material.
[0129] Example 6 - Wet coating with 2000 ppm ammonium niobium oxalate / heat treatment at 250°C
[0130] The lithium metal oxide particles obtained after the water washing process were dried and then subjected to a secondary heat treatment at 250°C. In addition, a positive electrode active material having a first coating layer containing a first niobium compound formed on the surface of the primary particles and a second coating layer containing a first niobium compound and a second niobium compound formed on the surface of the secondary particles was prepared by the same method as in Example 5.
[0131] Example 7 - Wet coating with 2000 ppm ammonium niobium oxalate / heat treatment at 350°C
[0132] The lithium metal oxide particles obtained after the water washing process were dried and then subjected to a secondary heat treatment at 350°C. In addition, a positive electrode active material having a first coating layer containing a first niobium compound formed on the surface of the primary particles and a second coating layer containing a first niobium compound and a second niobium compound formed on the surface of the secondary particles was prepared by the same method as in Example 5.
[0133] Example 8 - Wet coating with 2000 ppm ammonium niobium oxalate / heat treatment at 450°C
[0134] The lithium metal oxide particles obtained after the water washing process were dried and then subjected to a secondary heat treatment at 450°C. In addition, a positive electrode active material having a first coating layer containing a first niobium compound formed on the surface of the primary particles and a second coating layer containing a first niobium compound and a second niobium compound formed on the surface of the secondary particles was prepared by the same method as in Example 5.
[0135] Comparative Example 5 - Wet coating of 4000 ppm of ammonium niobium oxalate (pH of the solution set to 5 or above)
[0136] Based on 1 mol of the positive electrode active material precursor prepared in Preparation Example 1, 1.05 mol of LiOH·H2O (Sanquan Chemical, battery grade), ZrO2 (Aldrich, 4N) and Al(OH) 3( Aldrich, 4N) were uniformly mixed and mixed so that Zr was 3400 ppm and Al was 280 ppm to prepare a mixture.
[0137] The mixture is placed in a tube furnace and oxygen is introduced for calcination, then cooled to room temperature, and then pulverized to prepare a calcined body powder. The calcination conditions are heat treatment at 480°C for 5 hours and then maintained at 700 to 750°C for 16 hours, with a heating rate of 5°C / minute. Then, after cooling to room temperature, the calcined body powder is pulverized and classified to prepare lithium metal oxide particles in the form of secondary particles containing a plurality of primary particles.
[0138] Next, for the water washing process, 2.8818 g of ammonium niobium oxalate was added to 100 g of distilled water (DIwater) and stirred for 10 minutes, and then LiOH was added and the pH of the solution was made to reach 5 or above to prepare a suspension caused by the precipitation of LiNbO3, and then 250 g of the lithium metal oxide particles were added and stirred for 10 minutes to obtain lithium metal oxide particles having a coating layer containing the same lithium niobium compound (LiNbO3) formed on the surface of the primary particles and the surface of the secondary particles.
[0139] Then, the lithium metal oxide particles having the coating layers containing the same niobium compound (LiNbO 3 ) formed on the surfaces of the primary particles and the secondary particles were dried using a spray dryer and then subjected to a secondary heat treatment at 300° C. for 5 hours to prepare a positive electrode active material.
[0140] (Experimental Example 1) Evaluation of electrochemical characteristics
[0141] Electrochemical characteristics were evaluated after preparing 2032 coin-type half cells using the positive electrode active materials prepared according to Comparative Examples 1 to 3, Reference Examples 1 to 2, and Examples 1 to 6.
[0142] (1) Preparation of coin-type half-cell
[0143] Specifically, the positive electrode active material, polyvinylidene fluoride binder (trade name: KF1100) and Denka black conductive material are mixed in a weight ratio of 92.5:3.5:4, and the mixture is added to N-methyl-2-pyrrolidone (N-Methyl-2-pyrrolidone) solvent so that the solid content in the solvent reaches about 30 weight % to prepare a slurry of the positive electrode active material.
[0144] The slurry was coated on an aluminum foil (Al foil, thickness: 15 μm) as a positive electrode collector using a doctor blade, dried, and then pressed to prepare a positive electrode. The positive electrode loading was about 14.6 mg / cm 2 , the compression density is about 3.1g / cm 3 .
[0145] A 2032 coin-type half-cell was prepared by a conventional method using the positive electrode, a lithium metal negative electrode (thickness 200 μm, Honzo metal), an electrolyte and a polypropylene separator. The electrolyte was as follows: 1M LiPF6 was dissolved in a mixed solvent of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate (EMC) (mixing ratio EC: DMC: EMC = 3: 4: 3 volume %) to prepare a mixed solution, and 1.5 wt% of vinylene carbonate (VC) was added thereto.
[0146] (2) Evaluation of 0.1C discharge capacity at 25°C and initial resistance at room temperature
[0147] The coin-type half-cell prepared in (1) was aged at room temperature (25° C.) for 10 hours and then subjected to a charge and discharge test.
[0148] For capacity evaluation, 215 mAh / g was used as the reference capacity, and the charge and discharge conditions were CC / CV 2.5 to 4.25 V, 1 / 20 C cut-off. For initial capacity, the test was performed under 0.1 C charge / 0.1 C discharge conditions.
[0149] The resistance was calculated by measuring the voltage change within 60 seconds after applying a 0.2 C discharge current when the battery was charged to 100% at 0.2 C and 4.25 V. The results are shown in Table 1 below.
[0150] It can be confirmed from the following Table 1 that the initial efficiency at room temperature of the battery using the positive electrode active material of Comparative Example 1 without a coating layer is significantly reduced.
[0151] In addition, the battery using the positive electrode active material of Comparative Example 2 formed with the coating layer containing the boron compound had a very high initial resistance at room temperature.
[0152] At the same time, compared with the batteries using the positive electrode active materials of Comparative Examples 3 and 4 having a coating layer containing a niobium compound and formed by a dry coating method, the batteries using the positive electrode active material of the embodiment in which the first coating layer and the second coating layer containing a niobium compound are formed on the surfaces of the primary particles and the secondary particles by a wet coating method have excellent initial efficiency at room temperature and a significantly reduced initial resistance value.
[0153] Figure 1a The 0.1C discharge capacity and initial resistance value according to the niobium content are shown in FIG. Figure 1b 0.1C discharge capacity and initial resistance value according to the secondary heat treatment temperature when the niobium content is 2000 ppm are shown in FIG.
[0154] from Figure 1a It can be confirmed that the niobium content is optimal when it is 2000ppm. Figure 1b It can be seen that the best values are obtained when the niobium content is 2000 ppm and the secondary heat treatment temperature is 300°C to 350°C.
[0155] (Experimental Example 2) Evaluation of Life and Resistance Increase Rate at 45°C
[0156] Coin-type half-cells were prepared using the positive electrode active materials of Comparative Examples 1 to 3, Reference Examples 1 to 2 and Examples 1 to 6 by the same method as in Experimental Example 1 (1), and then aged at room temperature (25° C.) for 10 hours before performing charge and discharge tests.
[0157] For capacity evaluation, 215 mAh / g was used as the reference capacity, and the charge and discharge conditions were CC / CV 2.5 to 4.25 V, 1 / 20 C cut-off. For initial capacity, the test was performed under 0.2 C charge / 0.2 C discharge conditions.
[0158] For high temperature cycle life characteristics, the ratio of the 30th capacity to the first capacity was measured after 30 tests at high temperature (45°C) under 0.3C charge / 0.3C discharge conditions. For resistance, the voltage change after applying the discharge current for 60 seconds when the battery was charged to 100% at 4.25V was measured, and the resistance was calculated. The results are shown in Table 1 below.
[0159] It can be confirmed from Table 1 below that the battery using the positive electrode active material of Comparative Example 1 without a coating layer has a deteriorated life characteristic at room temperature, a significantly reduced resistance increase rate, and a significantly reduced initial efficiency.
[0160] In addition, the battery using the positive electrode active material of Comparative Example 2 formed with the coating layer containing the boron compound had a very high initial resistance at room temperature.
[0161] Meanwhile, the battery using the positive electrode active material of the embodiment having a coating formed by coating the niobium compound by a wet coating method has excellent initial efficiency and significantly reduced initial resistance value, compared with the battery using the positive electrode active materials of Comparative Examples 3 and 4 having a coating layer containing a niobium compound and formed by a dry coating method.
[0162] On the other hand, the positive electrode active material of Comparative Example 5, in which the surfaces of the primary particles and the secondary particles contained the same niobium compound (ie, LNbO 3 ), had a larger initial resistance value and a higher resistance increase rate at high temperature than that of the examples.
[0163]
Table 1
[0164]
[0165] on the other hand, Figure 2a The life span and resistance increase rate at high temperature according to the niobium content are shown in FIG. Figure 2b The high temperature life and the high temperature resistance increase rate according to the secondary heat treatment temperature when the niobium content is 2000ppm are shown in FIG. In addition, for the positive electrode active material prepared according to Comparative Example 2 with a boron coating formed thereon and the positive electrode active material prepared according to Example 2 with a coating containing a niobium compound formed on the interface of the primary particles and the interface of the secondary particles, the life and the resistance increase rate are shown in FIG. Figure 2c middle.
[0166] Reference Figure 2a The best value is shown when the niobium content is 2000ppm.
[0167] In addition, from Figure 2b It was confirmed that when the secondary heat treatment temperature was 300° C. to 350° C., both the life and the resistance increase rate characteristics at high temperatures were excellent.
[0168] from Figure 2c It was confirmed that the battery using the positive electrode active material of the example had excellent life characteristics at high temperatures and a significantly reduced resistance increase rate at high temperatures.
[0169] (Experimental Example 3) TEM analysis of primary particle interface components
[0170] The positive electrode active material prepared in Example 3 was cross-sectioned using a FIB (focused ion beam, SEIKO 3050SE) and then analyzed using a TEM (transmission electron microscope, JEOL 2100F) analysis device.
[0171] Specifically, the cross section of the positive electrode active material was subjected to element mapping analysis and the interface components of the primary particles were subjected to line scanning analysis. The results are shown in Figure 3a to Figure 3c middle.
[0172] from Figure 3a to Figure 3c It can be confirmed that the primary particle interfaces of the positive electrode active material prepared according to Example 3 are uniformly coated with niobium.
[0173] (Experimental Example 4) TEM Analysis of Primary Particle Interface Structure
[0174] The positive electrode active material prepared in Example 3 was cross-sectioned using a FIB (focused ion beam, SEIKO 3050SE) and then analyzed using a TEM (transmission electron microscope, JEOL 2100F) analysis device.
[0175] Specifically, the structure of the primary particle interface in the cross section of the positive electrode active material was analyzed and the results are shown in Figure 4 middle.
[0176] from Figure 4 It was confirmed that the positive electrode active material prepared according to Example 3 formed a coating layer containing amorphous niobium oxide with a thickness of 2 to 3 nm on the primary particle interface.
[0177] (Experimental Example 5) Analysis of Lithium on Primary Particle Interface Using EELS
[0178] The positive electrode active material prepared in Example 3 was cut into sections using a FIB (focused ion beam, SEIKO 3050SE), and the sections of the positive electrode active material were analyzed using a STEM (scanning transmission electron microscope, JEOL ARM 200F) analysis device. Figure 5a .
[0179] Next, if Figure 5a As shown, the interface of the primary particles of the positive electrode active material was analyzed using EELS (electron energy loss spectroscopy, GATAN GIF Quantum ER 965) equipment to determine whether the coating layer at the interface of the primary particles contained lithium. The analysis results are shown in Figure 5b .
[0180] Reference Figure 5a and Figure 5b , at the interface of the primary particle surface (i.e., Figure 5bNo lithium was observed at site 2.
[0181] Therefore, when considering Figure 3b , Figure 3c , Figure 5a and Figure 5b When the results are shown in FIG. 1 , in the case of preparing the positive electrode active material according to this embodiment, the first coating layer located on the surface of the primary particle is a coating layer that does not contain lithium (ie, contains niobium oxide).
[0182] (Experimental Example 6) SEM Analysis of Secondary Particle Surfaces
[0183] The surface of the positive electrode active material prepared in Example 3 was analyzed by SEM (scanning electron microscope, JEOL JSM-6610) and EDS. Figure 6 middle.
[0184] from Figure 6 It can be confirmed that the positive electrode active material prepared according to this example is also uniformly coated with the coating layer containing the niobium compound on the surface of the secondary particles.
[0185] (Experimental Example 7) TEM analysis of secondary particle surface components
[0186] The positive electrode active material prepared in Example 3 was cross-sectioned using a FIB (focused ion beam, SEIKO 3050SE) and then analyzed using a TEM (transmission electron microscope, JEOL 2100F) analysis device.
[0187] Specifically, the cross section of the positive electrode active material is elementally mapped as shown in Figure 7 middle.
[0188] from Figure 7 It can be confirmed that the positive electrode active material prepared according to this example is uniformly coated with the coating layer containing the niobium compound on the surface of the secondary particles.
[0189] (Experimental Example 8) TEM Analysis of Secondary Particle Surface Structure
[0190] The positive electrode active material prepared in Example 3 was cross-sectioned using a FIB (focused ion beam, SEIKO 3050SE) and analyzed using a TEM (transmission electron microscope, JEOL 2100F) analysis device.
[0191] Specifically, the structure of the secondary particle surface portion of the positive electrode active material is analyzed in cross section. Figure 8 middle.
[0192] from Figure 8It was confirmed that a coating layer containing amorphous niobium oxide having a thickness of 20 to 30 nm was formed on the interface of the secondary particles of the positive electrode active material prepared according to this example.
[0193] (Experimental Example 9) Qualitative Analysis of Secondary Particle Surfaces Using XPS
[0194] The surface XPS (X-ray photoelectron spectroscopy) analysis of the positive electrode active material prepared in Example 3 is shown in Fig. 9 Peak analysis uses only 3d 5 / 2 Peak value.
[0195] Reference Fig. 9 In the positive electrode active material prepared according to this embodiment, a second coating layer containing the first niobium compound and the second niobium compound is formed on the surface of the secondary particles. At this time, the niobium compound contained in the second coating layer is Nb2O5 and LiNbO3, which are present in an amount of 84.3 at% and 15.7 at% respectively, based on the total amount of the first niobium compound and the second niobium compound.
[0196] The present invention can be implemented in various ways and is not limited to the embodiments described. A person skilled in the art of the present invention can understand that the present invention can be implemented in other specific ways without changing the technical concept or essential features of the present invention. Therefore, it should be understood that the above embodiments are exemplary in all aspects and are not intended to limit the present invention.
Claims
1. A positive electrode active material for a lithium secondary battery, wherein, the positive electrode active material is in the form of secondary particles containing a plurality of primary particles and is a lithium metal oxide particle that satisfies the following Chemical Formula 1, the positive electrode active material includes: a first coating located on at least a part of the surface of the primary particles; and a second coating located on at least a part of the surface of the secondary particles, the first coating contains a first niobium compound, the second coating contains the first niobium compound and a second niobium compound whose components are different from those of the first niobium compound, [Chemical Formula 1] Li x Ni a Co b Mr c M1 d M2 e O2 In Chemical Formula 1, M1 and M2 are each at least one of Zr, Ti, Mg, Al, Ni, Mn, Zn, Fe, Cr, Mo, and W, x is 0.90 ≤ x ≤ 1.07, a is 0.80 ≤ a < 1, b is 0 < b ≤ 0.3, c is 0 < c ≤ 0.3, d is 0 < d < 0.01, e is 0 < e < 0.01, and a + b + c + d + e = 1.
2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein, the primary particles on which the first coating is located are inside the secondary particles.
3. The positive electrode active material for a lithium secondary battery according to claim 1, wherein, the first niobium compound does not contain lithium.
4. The positive electrode active material for a lithium secondary battery according to claim 1, wherein, at least one of the first niobium compound and the second niobium compound contains an amorphous structure.
5. The positive electrode active material for a lithium secondary battery according to claim 3, wherein, the first niobium compound is at least one of Nb2O5, NbO, and NbO2.
6. The positive electrode active material for a lithium secondary battery according to claim 1, wherein, the second niobium compound is at least one of LiNbO3, Nb2O5, Li3NbO4, and LiNb3O8.
7. The positive electrode active material for a lithium secondary battery according to claim 1, wherein, the average thickness of the first coating is 5 nm or less.
8. The positive electrode active material for a lithium secondary battery according to claim 1, wherein, the average thickness of the second coating is 30 nm or less.
9. The positive electrode active material for a lithium secondary battery according to claim 1, wherein, the second niobium compound is LiNbO3, based on the total first niobium compound and second niobium compound contained in the positive electrode active material, the content of LiNbO3 is 15.7 at% or more.
10. The positive electrode active material for a lithium secondary battery according to claim 1, wherein, based on the total positive electrode active material, the content of niobium in the positive electrode active material is 4000 ppm or less.
11. A method for preparing a positive electrode active material for a lithium secondary battery, which includes: a step of preparing a niobium-containing coating composition; a step of mixing a metal precursor and a lithium raw material and then calcining to obtain a calcined body; a step of adding the coating composition and the calcined body to prepare a mixture; and a step of drying the mixture and then performing heat treatment, the heat treatment is performed at 100 degrees to 500 degrees, Among them, the step of preparing the niobium-containing coating composition is carried out by a method of mixing ammonium niobium oxalate in distilled water. The positive electrode active material is in the form of secondary particles containing a plurality of primary particles and is a lithium metal oxide particle satisfying the following Chemical Formula 1, and The positive electrode active material comprises: A first coating located on at least a part of the surface of the primary particles; And A second coating located on at least a part of the surface of the secondary particles, wherein the first coating contains a first niobium compound, The second coating contains the first niobium compound and a second niobium compound having a component different from that of the first niobium compound, [Chemical Formula 1] Li x Ni a Co b Mr c M1 d M2 e O2 In Chemical Formula 1, M1 and M2 are each at least one of Zr, Ti, Mg, Al, Ni, Mn, Zn, Fe, Cr, Mo, and W, x is 0.90 ≤ x ≤ 1.07, a is 0.80 ≤ a < 1, b is 0 < b ≤ 0.3, c is 0 < c ≤ 0.3, d is 0 < d < 0.01, e is 0 < e < 0.01, and a + b + c + d + e = 1.
12. The method for preparing a positive electrode active material of a lithium secondary battery according to claim 11, wherein The heat treatment time of the heat treatment step is 3 hours to 10 hours.
13. A lithium secondary battery comprising: A positive electrode containing the positive electrode active material according to any one of claims 1 to 10; A negative electrode; and A non-aqueous electrolyte.
Citation Information
Patent Citations
Positive electrode active material particles, and positive electrode and all-solid-state battery using same
US20150024280A1
KR20190079526A